Achieving Future Competencies: Integrating Project-Based Learning and Simulation to Develop 21st Century Skills - Yusri, Radhya; Cesaria, Anna; Yusof, Anuar Mohd.; Delyana, Hafizah; Rahmi, Rahmi; Haryono, Yulia (FKIP Universitas Lampung, 2025)
This study aims to develop students' skills through the integration of project-based learning and simulation. This study used mixed methods by involving 30 students of the Mathematics Education Study Program at Universitas PGRI Sumatera Barat as research subjects. Data collection was conducted through observations of five meetings and semi-structured interviews with nine students of various academic ability level, including high, medium, and low. The research instrument for quantitative data was an observation sheet, while for qualitative data, a semi-structured interview sheet was used. The data obtained were analyzed using descriptive statistical analysis techniques for quantitative data and thematic analysis for qualitative data. The results of the study showed that the students' skills were not evenly distributed. Group collaboration in learning proved to be successful in increasing cooperation skills up to the high category, which indicates the effectiveness of learning in creating active interactions between students. However, other skills, such as creativity, communication, critical thinking, and innovation, are still in the medium category, which indicates that they still need further improvement and development. This study concludes that the integration of project-based learning and simulation has a positive effect on the abilities of students with uneven abilities. The integration of these learning approaches works synergistically by effectively linking theory and practice. Through project-based learning, students are encouraged to take an active role in designing, managing, and completing projects that directly contribute to their skill development. On the other hand, simulation functions as a complement that strengthens the effectiveness of project-based learning by presenting a real representation of the project by visualizing abstract concepts and allowing students to test the solutions they develop based on the project results. Keywords: ability, competency, project-based learning, simulation, skills.